Assistência ao planejamento familiar na perspectiva de usuárias e enfermeiros do Programa Saúde da Família - Moura, Escolástica Rejane Ferreira (2003)
Recognizing problems ín the quality of the attendance to the Family planning offered at our Country and, particularly, ín Ceará, we decided to accomplish the present study. It is an evaluation Research, accomplished in the Health Cell of Baturité-CE, with the objective of evaluating the attendance to the Family planning in what refers to the offer and the free choice of the birth-control methods, the information given to the customers and the professional technícal competence; and discover the dynamics of the interpersonal relationship nursecustomer, of the mechanism of the users’ accompaniment and an appropriate Services net of Family planning. The research had a qualitative and quantitativo approaching. The data were collected in the period of July to September 2003 through the free observation and a structured route of interview, having been most accomplished in the Family Health Units (USF) and other, specificaily with nurses, accomplished in their homes. The data of the interviews were written for the researcher concomitantly, in the own schedules; the originating data ofthe observation were registered in a diaiy. The participants were 29 male nurses and 50 users of Services of Family planning of the eight municipal districts that compose the respective of Health Cell, involving Services of the urban and rural zones. We used the Analysis of Content Method, following the technique oFanalysis categórica! in the organization ofthe results. We adopted the six elements of the quality ofthe attendance to the Family planning proposed by Judith Bruce, as theoretical referential. The results revealed marks and lines of the six elements of the quality (offer and liberate choice of the birthcontrol methods, information given to the customer, professional technícal competence, interpersonal relationship nurse-customer, the users’ accompaniment and appropriate Services net) in the speeches presented by the nurses and users with relationship to the developed practice and received, respectively. Even so, these marks and lines appeared incomplete and other superficial times, in a demonstration that there was not an axis that guides for the actions, that happened in the rhythm and in the quality dimension that each professional judged appropriate or convenient. This way, we defended the idea that nurses and users ofthe Services of family planning of the universe of the study have a perception refined regardíng the quality elements, though they need to be more determined to their effectivity in the practice. More over, the users identified the masculine participation as more an element ofthe quality to the family planning, what was reinforced by the nurses. They also identified the registration on the part of the professionals as innovators to Bruce’s conceptual structure, On the other hand, the work in team was identified by the researcher / author as being an essenti al element to the quality, in the current context, in that the attendance to the family planning is offered basically by Family Health Program,